Immediate effect of pain neuroscience education for recent onset low back pain: an exploratory single arm trial. (20th October 2019) - Louw, Adriaan; Farrell, Kevin; Choffin, Breanna; Foster, Brooke; Lunde, Grace; Snodgrass, Michelle; Sweet, Robert; Weitzel, Matthew; Wilder, Rebecca; Puentedura, Emilio J.
ABSTRACT: Study Design : A prospective, single-arm, pre-postintervention study. Objective : To determine the preliminary usefulness of providing pain neuroscience education (PNE) on improving pain and movement in patients presenting with non-chronic mechanical low back pain (LBP). Background : PNE has been shown to be an effective intervention for the treatment of chronic LBP but its usefulness in patients with non-chronic LBP has not been examined. Methods : A single group cohort pilot study was conducted. Eighty consecutive patients with LBP < 3 months completed a demographics questionnaire, leg and LBP rating (Numeric Pain Rating Scale – NPRS), disability (Oswestry Disability Index), fear-avoidance (Fear-Avoidance Beliefs Questionnaire), pain catastrophizing (Pain Catastrophizing Scale), central sensitization (Central Sensitization Inventory), pain knowledge (Revised Neurophysiology of Pain Questionnaire), risk assessment (Keele STarT Back Screening Tool), active trunk flexion and straight leg raise (SLR). Patients received a 15-minute verbal, one-on-one PNE session, followed by repeat measurement of LBP and leg pain (NPRS), trunk flexion and SLR. Results : Immediately after intervention, LBP and leg pain improved significantly (p < 0.001), but the mean change did not exceed minimal clinically important difference (MCID) of 2.0. Active trunk flexion significantly improved (p < 0.001), with the mean improvement (4.7 cm) exceeding minimal detectible change (MDC). SLR improved significantly (p = 0.002), but mean change did not exceed MDC. Conclusions : PNE may be an interesting option in the treatment of patients with non-chronic mechanical LBP. The present pilot study provides the rationale for studying larger groups of patients in controlled studies over longer periods of time.